Identifikasi Penyebab Kematian Domba Melalui Bedah Bangkai di Desa Pantai Mekar, Muara Gembong, Kabupaten Bekasi - Sharon Aurellia; Armando Balses Ishimora; Dwi Rofifah Putri Jania; Putri Ramadhanty; Aisyah Aisyah; Alfina Zalfa Suryono; Rafida Nisa Maghfiroh; Siti Magfiroh; Antonius Anre Sianturi; Ranady Perwira Nuruzzaman; Akhmad Endang Zainal Hasan; Vetnizah Juniantito (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2023)
Sheep breeders generally raise their sheep by releasing and allowing their livestock to graze wildly. This causes the sheep to receive feed intake with unbalanced nutrition. One of the student programs in the KKN-T IPB University in Pantai Mekar Village, Muara Gembong District, Bekasi Regency, were checking physical conditions, socializing management of sheep maintenance and distribution of vitamin B complex which to improve the health of the sheep. It was reported that four sheep were found dead after B complex vitamin administration to in four days. The sheep cadavers were brought to the School of Veterinary and Biomedical Sciences, IPB to undergo carcass surgery or necropsy to reveal the cause of death. The results of necropsy found Haemonchus contortus worm infestation in the abomasum of sheep, accompanied by accumulation of fluid under the skin, chest cavity, stomach, and lungs. The cause of death of the four sheep based on necropsy was caused by severe infestation of the Haemonchus contortus type of worm and malnutrition, which lead to hypoalbuminemia and progressed to edema in the lungs, which resulted in shortness of breath (dyspnea). In this case the necropsy results showed that the administration of vitamin B complex was not the cause of the death of the sheep.